Extracellular Matrix Protein Laminin Induces Matrix Metalloproteinase-9 in Human Breast Cancer Cell Line MCF-7 - Pal, Sekhar (Springer Netherlands, 2014)
Studies on interaction of tumor cells with extracellular matrix (ECM) components showed increased extracellular protease activity mediated by the family of matrix metalloproteinases (MMPs). Here we studied the effect of human breast cancer cell line MCF-7-laminin (LM) interaction on MMPs and the underlying signaling pathways. Culturing of MCF-7 cells on LM coated surface upregulated MMP-9 expression as well as reduced tissue inhibitor of metalloproteinases-1 (TIMP-1) expression. LM induced MMP-9 expression is abrogated by the blockade of α(2) integrin. Inhibitor studies indicate possible involvement of phosphatidyl-inositol-3-kinase (PI3K), extracellular signal regulated kinase (ERK) and nuclear factor-kappaB (NF-κB) in LM induced signaling. LM treatment also enhanced phosphorylation of FAK (focal adhesion kinase), PI3K, ERK; nuclear translocation of ERK, pERK, NF-κB and cell migration. Our findings indicate that, binding of MCF-7 cells to LM, possibly via α(2)β(1) integrin, induces signaling involving FAK, PI3K, ERK, NF-κB followed by upregulation of MMP-9 and cell migration.